Role of spleen-derived monocytes/macrophages in acute ischemic brain injury - Kim, Eunhee (Nature Publishing Group, 2014)
Monocytes/macrophages (MMs), mononuclear phagocytes, have been implicated in stroke-induced inflammation and injury. However, the presence of pro-inflammatory Ly-6C(high) and antiinflammatory Ly-6C(low) monocyte subsets raises uncertainty regarding their role in stroke pathologic assessment. With recent identification of the spleen as an immediate reservoir of MMs, this current study addresses whether the spleen-derived MMs are required for stroke pathologic assessment. We observed that the spleen was contracted in poststroke animals and the contraction was accompanied by decreased number of Ly-6C(high) and Ly-6C(low) subsets in the spleen. The deployment of these subsets from the spleen temporally coincided with respective increases in the ischemic brain. Compared to mice with the spleen, mice receiving a splenectomy just before the stroke displayed less accumulation of Ly-6C(high) and Ly-6C(low) MMs in the brain. Despite the reduced accumulation of both subsets, infarct size and swelling were not reduced in the asplenic mice. The dissociative findings of infarct size and extent of MM infiltration in the postischemic brain indicate minimal involvement of spleen-derived total MMs in acute infarct development. Selective Ly-6C(high) or Ly-6C(low) MM targeting is suggested to address the contribution of the individual subset to acute stroke pathologic assessment.